Analysis On Distraction While Driving- A Case Study On Staffs And Students Of Engineering Campus, Universiti Sains Malaysia - Mustafa, Nur Fatin (Universiti Sains Malaysia, 2017)
The road traffic accidents and injuries were increased by each year. Mostly the accidents that occurred will involving the distracted drivers while driving. Distraction while driving is any activity that could divert a person's attention away from the primary task of driving. These types of distractions including texting, using a smartphone, eating and drinking, talking to passengers, using a navigation system, adjusting radio, CD player, or MP3 player. Until now, there is no in depth study that focusing on the distraction while driving in Malaysia. Therefore, the objective of this study is to identify the drivers’ perception toward distraction while driving by using questionnaire survey based on Susceptibility to Driver Distraction Questionnaire (SDDQ), to analyze the driving distraction based on the secondary task given in the experimental survey and to determine the relationship between socio-demographic factors with drivers’ distraction based on SDDQ and experimental tasks. The results from this study showed that the most drivers have involved in driving distraction influenced by perceived social norms toward voluntary distraction. Radio-operating and phone texting were identified as the most distraction tasks among the respondents involved in this study. It is based on the total eye glance of the respondent from their focus in this tasks. Furthermore, phone texting also be ranked as the most distracting tasks by 19 respondents out of 21 number of respondents. The relationship between socio-demographic with drivers’ distraction based on SDDQ and experimental tasks show that age and gender as the influenced parameter that correlated with all the question in SDDQ and experimental tasks.